The prevalence of parent-teacher interaction in developing countries and its effect on student outcomes. (November 2019) - Li, Guirong; Lin, Millie; Liu, Chengfang; Johnson, Angela; Li, Yanyan; Loyalka, Prashant
Abstract: Empirical evidence from developed countries supports the idea that parent-teacher interaction is high and improves student outcomes. The evidence from developing countries is, however, decidedly mixed. Using longitudinal data from nearly 6000 students and their 600 teachers in rural China, we show the prevalence of parent-teacher interaction is generally much lower than that of developed countries. We also show parent-teacher interaction, when it exists, can have positive effects on raising academic achievement and reducing learning anxiety. We demonstrate that the prevalence and effectiveness of parent-teacher interaction in a developing country context varies considerably due to both demand-side and supply-side factors. Highlights: The prevalence of parent-teacher interaction is low in rural China, especially among disadvantaged students. Parent-teacher interaction has positive effects on raising academic achievement and reducing learning anxiety. The prevalence and effectiveness of parent-teacher interaction varies by both demand-side and supply-side factors.